Newman Procedure dalam Menganalisis Kesalahan Siswa SMP dalam Menyelesaikan Soal Setara PISA - Susanti, Susanti (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2019)
This study aims to identify students’ errors in solving problem equals to PISA’s based on Newman procedures. Qualitative-descriptive research was used in conducting this study and the subjects were third-grade students at SMP Unggul Sigli in year 2017/2018. Data was collected using tests and interviews. The instrument of this study was a sheet consisting of 5 (five) mathematical questions that composed equivalent to PISA’s problem. Analyzing students’ errors was guided by analyzing procedures developed by Newman which contain 5 (five) kinds of error, they are (1) reading error; (2) understanding error; (3) transformation error; (4) processing skill error; and (5) writing error. The result showed the percentage of each kind of errors made by students which detailed as follows, reading error comprised 37,1% of students; error in problem understanding made up 47%; 73% of subjects made error in transforming; 80% of students had error in processing; and error in writing final answer made up 78,1% of them. By analyzing the percentage, it is identified that the three most common mistakes are processing error, transformation error, and error in writing a final answer.